THE EFFECT OF HYPOXIA ON THE MORPHOLOGICAL AND FUNCTIONAL QUALITIES OF THE INTERALVEOLAR CAPILLARIES OF THE LUNGS AFTER ACUTE PHYSICAL LOAD IN THE EXPERIMENT - Sultanova, T.S.; Akbarov, E.C.; Yagubova, S.M. (World of Medicine and Biology, 2023)
The purpose the study was a comprehensive study of the structural restructuring of the respiratory section of the lungs during physical exertion in the experiment, the determination of the morphological equivalent of acute fatigue of the air-blood barrier. The study was performed on 30 laboratory-outbred male rats weighing 120.0–150.0 g. Histological and electron-microscopic methods were used. Experimental findings once again prove that alveolar hyperventilation affects respiratory alveolocytes and the endothelium of interalveolar capillaries, predetermining the further course of the pathological process in the aero-hematic barrier. Analysis of the available factual data on the submicroscopic reorganization of the endothelium in the early stages of hypoxia will allow us to agree with the opinion about deep violations of the pulmonary capillaries during acute limiting physical activity. An increase in the permeability of the alveolar-capillary membrane, pulmonary vascular resistance, and a violation of the mechanics of breathing with the development of alveolar hypoxia is currently recognized as the main pathogenic factors of hypoxemia and damage to the lung parenchyma.